Lignin as Alternative Reinforcing Filler in the Rubber Industry: A Review - Mohamad Aini, Nor Anizah; Othman, Nadras; Hussin, M. Hazwan; Sahakaro, Kannika; Hayeemasae, Nabil (Frontiers in Materials, 2020)
Lignin has potential as a reinforcing filler and to become an alternative to carbon black in the rubber industry. This is because it is formed from cheaper materials with abundant annually renewable sources and has low weight, high biological efficiency, and wide ecological adaptability. The utilization of bio-filler in the rubber industry has garnered increasing attention from researchers due to increasing environmental concerns over the toxic effects of carbon black on health and the environment. This article is intended to summarize current efforts in the development of a green and sustainable rubber product. Instead of focusing on silica and alternative rubber matrix-like guayule and Russian dandelion, it looks at lignin, which also has potential as a reinforcing filler and can enable the development of competitive green rubber composites. Lignin has several special characteristics such as good mechanical, physico-chemical, biodegradability, and antioxidant properties and excellent thermal stability. However, the incorporation of lignin in a rubber matrix is not straightforward, and this needs to be overcome with certain suitable solutions because of the polarity of lignin molecules, which contributes to strong self-interactions. Consequently, chemical modification of lignin is often used to improve the dispersion of lignin in elastomers, or a compatibilizer is added to enhance interfacial adhesion between lignin and the rubber matrix. This review attempts to compile relevant knowledge about the performance of lignin-filled rubber composite using different approaches such as mixing method, surface modification, hybrid fillers, etc. This study is expected to gain significant interest from researchers globally on the subject of lignin-based rubber composites and the advancement of development in green rubber products.